Teaching English to Young Learners in China and Ukraine - Jiang, Haozhe (Educational Challenges, 2022)
The research need is determined by active educational partnership between People’s Republic of China and other countries, and Ukraine too. The collaboration promotes the comparative pedagogical researches of educational process of both countries. The content of the Recommendations of the European Council, the recommendations of the British Council on language education demand new requirements for the language quality teaching and learning, the development of new forms, methods and tools in the world. In this regard, it is important to study the principles of teaching English in China and Ukraine. The purpose is to outline the basics of teaching English at school in China and Ukraine. Methodology. The analytical method is used to investigate English teaching process; the comparative method is used to analyze the experience of teaching English in two countries. Results. Teaching English in China as the new reality shows that the National Curriculum has made English a compulsory subject for Chinese schools. The teaching method in China differs greatly from the international, Western one. It is based on information memorization, as well as it is focused on the study of the Chinese language, culture, and history. Only in international or private schools in China, teaching is conducted according to international standards. To learn English, the British or American model of learning is used, based on communication and discussing learning material and new information, and not on copying or memorizing it. According to the new Curriculum, for young learners, English is taught as a subject two or three hours a week in 1-3 grades, three or four hours a week in 4-6 grades. International English curricula focus on communication and skills, but the Ministry of Education of the People’s Republic of China has decided to expand its goals to national ones and adapt the international English curriculum for Chinese young learners. Experience of teaching English in Ukraine shows that English is studied from the 1st grade, from the age of 6, according to the “New Ukrainian School” curriculum. The British Council in Ukraine took care of teaching English to young learners greatly. It trains a lot of English teachers in Ukraine. Teaching English to young learners has moved very much in providing the communicative approach. At English lessons children learn English by communication using pictures, songs, poems, fairy tales, short plays, games and holidays. Conclusion. China becomes the world leader in the number of English learners as it is necessary for schools, Universities, and future careers. Now about 400 million Chinese learn English, there are more English learners in China than English speakers. The English teaching method is mostly old school, and traditional, but the situation is changing. Most Chinese consider that English is a necessary means of bringing China closer to the whole world. Ukrainian teachers and learners are more trained for the new requirements to teach and learn English due to the British Council’s help in Ukraine. The communicative approach is basically used for teaching English. Ukrainian teachers and learners have got a definite positive experience to teach and learn English successfully.